“The soul that dreams it shares the power it feels so well”: The Politics of Sympathy in the Abolitionist Verse of Williams and Yearsley - Mitchell, Robert (Romanticism on the Net, 2003)
AbstractIdentifying abolitionist poetry as an important site for investigating rhetorical transformations and innovations in late eighteenth century women’s poetry, this essay shows how poetic language generates sympathy. In reading women’s poetry in general, and abolitionist poetry in particular, we too often presume that they worked under the assumption that all readers would identify directly with representations of suffering. While William Cowper, writing before Helen Maria Williams and Ann Yearsley, opens up the problematic that all forms of sympathy might be mere narcissistic self-indulgence, Yearsley and Williams provide a model for and effectively limit such reflexive sympathy. For them, the process of sympathizing with an Other begins with the act of taking him or her into one’s own imaginative “domos.” But by actively embracing this narcissistic process, Williams and Yearsley are able to regulate such domestications of the slave’s pain. Williams controls whose identities merge, ensuring that the reader identifies with reformer rather than slaver. In contrast, Yearsley encourages wider-ranging imaginative acts of identification – one can identify with the “crafty merchant” of her “Poem on the Inhumanity of the Slave Trade” – but ensures through various poetic devices that such an act will reveal the disjunction between family and capital. By drawing out various theories of the working of sentiment, this essay makes visible sentimental poetry’s theoretical power: slavery poems by Williams and Yearsley operate as sophisticated theories of sympathetic identification.